Luteal phase stimulation versus follicular phase stimulation in poor ovarian responders: results of a randomized controlled trial - Joaquín Llácer; Belén Moliner; Lydia Luque; Andrea Bernabéu; Belén Lledó; Juan Carlos Castillo; Jaime Guerrero; Jorge Ten; Rafael Bernabéu (BMC, 2020)
Abstract Background In young women with poor ovarian response, luteal-phase ovarian stimulation (LPOS) is a potential method for collecting competent oocytes. The aim of this study was to assess the efficacy of LPOS compared with follicular phase ovarian stimulation (FPOS) in young women with poor ovarian response (POR). Methods This single-center, prospective, randomized pilot study compared LPOS and FPOS in women with POR fulfilling Bologna criteria who underwent in vitro fertilization at the Instituto Bernabeu. The primary outcome was the number of metaphase II (MII) oocytes obtained by follicular puncture. Results Sixty women were included in the study, with 27 women completing LPOS and 30 undergoing FPOS. There was no statistically significant difference in the number of MII oocytes obtained between the LPOS group and the FPOS group (2.1 ± 2.0 vs. 2.6 ± 2.2, p = 0.31). Length of stimulation was also similar in both groups (8.35 ± 2.8 vs. 8.15 ± 4.1 days, p = 0.69). Similarly, there was no significant difference in the follicle-stimulating hormone total dose, number of cumulus-oocyte complexes, survival rate, fertilization rate, or cancellation rate between groups. A significantly higher Ovarian Sensitivity Index was observed in the LPOS group versus the FPOS group (0.96 vs. 0.57, p = 0.037). Conclusion LPOS was comparable with FPOS in terms of efficacy and may improve ovarian responsiveness in young women with POR. Trial registration ClinicalTrials.gov identifier: NCT02625532 ; EudraCT identifier: 2015-003856-31 .